CORRELATES OF JOB SATISFACTION: SOME EVIDENCE FROM THE NATIONAL SURVEYS - Weaver, Charles N. (Academy of Management Journal, 1974)
The article presents a synthesis of correlation studies of job satisfaction in the U.S. Although there is a positive relationship between income and job satisfaction, there apparently is a stronger association between satisfaction with income and job satisfaction. Employees who report satisfaction with their housing situation are more likely to report job satisfaction. Meanwhile, there is little variation among the reports of job satisfaction at different levels of education. Satisfaction appear to be higher for employees in professional, farm and skilled blue-collar occupational categories than for workers in the unskilled category.